Applying the Food Choice Process Model to Ultra-Processed Food Consumption: The Role of Dietary Globalization and Quality Perceptions - Eda Luga; Gentjan Mehmeti (European Scientific Journal, ESJ, 2026)
This study examines the determinants of ultra-processed food (UPF) consumption frequency among young adults within the Food Choice Process Model, integrating macro-level (dietary globalization) and micro-level (perceptions of food quality, environmental awareness, and media exposure) influences. A survey was conducted with 310 young adults, and ordinal logistic regression analysis was used to test the hypothesized predictors of UPF consumption frequency.Results indicate that dietary globalization is positively and significantly associated with UPF consumption, supporting the hypothesis that exposure to international dietary patterns increases the likelihood of consuming ultra-processed products. In contrast, negative perceptions of international food quality are negatively associated with consumption frequency, confirming that unfavorable quality evaluations reduce UPF intake. Environmental awareness and exposure to internet and social media content do not emerge as statistically significant predictors.Overall, UPF consumption among young adults appears to be primarily shaped by globalization-related dietary exposure and evaluative perceptions of food quality, rather than environmental concerns or digital media influence. These findings provide empirical insight into the structural and cognitive drivers of contemporary dietary behavior and inform public health strategies aimed at reducing ultra-processed food consumption.